Of madams, mentors and mistresses: Conceptualising the female sex trafficker in the United States - Veldhuizen-Ochodničanová, Eva (International journal of law, crime and justice, 2021)
Sex trafficking constitutes a severe international issue, affecting 4.8 million victims worldwide, with those affected in the United States numbering in the thousands (Global Slavery Index, 2016). Despite this, little is known about the characteristics of sex traffickers, especially female sex traffickers. This paper aimed to increase our knowledge of female sex traffickers in the United States. 44 criminally prosecuted cases of sex trafficking involving female sex traffickers were examined, obtained through the Case Law Database within the Human Trafficking Knowledge Portal provided by the United Nations Office on Drugs and Crime. The study sought to explore characteristics of female sex traffickers in the United States with regards to the roles they hold, duties they perform and the makeup of their operations. Overall, findings demonstrated that women permeate the entire spectrum of sex trafficking crimes, from aiding and abetting to being ringleaders of sex trafficking rings.